2018
DOI: 10.1016/j.ijsu.2018.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery bypass graft readmission rates and risk factors - A retrospective cohort study

Abstract: CABG readmission rates remain high and are associated with insurance status and racial and socioeconomic markers. Further investigation is necessary to better delineate the underlying factors that relate racial and socioeconomic disparities to CABG readmissions. Understanding these factors will be key to improving healthcare outcomes and expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 44 publications
4
29
1
1
Order By: Relevance
“…Early effusions (the initial 15 postoperative days) are typically hemorrhagic, neutrophil predominant, and associated with operative trauma. Later effusions tend to be lymphocyte predominant and autoimmune in etiology [45]. After CABG, effusions are associated with low BMI, female gender, history of atrial fibrillation, history of heart failure, concurrent valve replacement, and history of anticoagulation [45].…”
Section: Pleural Effusionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early effusions (the initial 15 postoperative days) are typically hemorrhagic, neutrophil predominant, and associated with operative trauma. Later effusions tend to be lymphocyte predominant and autoimmune in etiology [45]. After CABG, effusions are associated with low BMI, female gender, history of atrial fibrillation, history of heart failure, concurrent valve replacement, and history of anticoagulation [45].…”
Section: Pleural Effusionsmentioning
confidence: 99%
“…Later effusions tend to be lymphocyte predominant and autoimmune in etiology [45]. After CABG, effusions are associated with low BMI, female gender, history of atrial fibrillation, history of heart failure, concurrent valve replacement, and history of anticoagulation [45]. Postoperative pleural effusion is the second most common cause of readmission in a CABG patient (22.5% of patients), and the need for thoracentesis is a poor prognostic sign [45,46].…”
Section: Pleural Effusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most, but not all, common medical and surgical disorders have worse outcomes in patients from distressed communities ( Table 1). [8][9][10][11][12][13][14][15][16][17][18][19][20][21] DOES LIVING IN A DISTRESSED COMMUNITY CAUSE WORSE OUTCOMES FROM SURGICAL PROCEDURES? Table 1 suggests that living in a distressed community is associated with worse outcomes from many medical disorders and from surgical interventions.…”
Section: How Do You Know If You Live In a Distressed Community?mentioning
confidence: 99%
“…In recent years, there have been many studies on risk factors related to CABG readmission [4][5][6][7] , however, few studies have established a complete model to predict the risk of CABG readmission [8][9][10] . At present, the risk prediction models of readmission after CABG are mainly from western countries such as the United States and Canada, but previous studies have shown that these models cannot be well applied to Chinese and the other Asian populations [11][12] .…”
Section: Introductionmentioning
confidence: 99%